The Archaeology of Childhood: Revisiting Mohenjodaro Terracotta - Ajay Pratap (Ancient Asia, 2016)
For long archaeologists have been perplexed that the excavated data are usually interpreted from an adult male perspective. The literature locating this and the concomitant rise of gendered archaeology thrives (Conkey and Spector 1984, Conkey and Gero 1999, Conkey 2005). However, in addition to andocentric biases in archaeology, there is also a tendency to overlook the evidence related with children that who are omnipresent, in all cultures. As this is true in the Indian context also, in this paper we shall suggest that terracotta objects provide an invaluable category of archaeological material for considering the archaeology of childhood.